Perancangan Dan Pengembangan E-Commerce Penjualan Ikan Teri Sibolga - Deden Ranco Biaga (Cattleya Darmaya Fortuna, 2022)
The anchovy shop is a company engaged in the sale of fish. The sales system used today is a conventional system, in which the buyer must come directly to the anchovy shop to see the products offered. One of the most supportive aspects is the existence of e-commerce facilities that can assist in the sales process or product offering. With e-commerce, companies can market their products online so consumers who are out of town can see and order products without having to come directly to the store. With the e- commerce system, the system certainly requires a good product data management or management. Based on the results of interviews from the anchovy shop and referring to the problems above, it is necessary to create a system that can solve all the problems that exist today.